Air pollution management in two colombian cities: case study (2005)
This document is a case study that focuses on the air pollution problems of Bogotá and Medellín. These are the largest; most populated and industrialized cities of Colombia. The document presents a brief description of the evolution of relevant institutional aspects. It describes the pollution problems of these cities, their sources, their effects on health and the measures to control and to prevent them. Following the framework of the WDR 20032, this document analyzes how society becomes aware ofair pollution problems and the mechanisms that have generated the decision to undertake air pollution control strategies. It also discusses the mechanisms which have been in place to balance legitimate, competing social interests, and the means by which the adopted solutions are executed. Finally, the document presents a series of lessons and recommendations.